Coupled CO2 capture and thermochemical heat storage of CaO derived from calcium acetate. Issue 5 (26th July 2020) - Sun, Chaoying; Yan, Xianyao; Li, Yingjie; Zhao, Jianli; Wang, Zeyan; Wang, Tao
Abstract: CaO/Ca(OH)2 thermochemical heat storage (THS) technology is considered to be one of the most promising technologies for large‐scale solar energy storage. However, the THS performance of raw CaO‐based materials decreases during multiple cycles. In this work, CaO derived from calcium acetate (Ac‐CaO) is prepared and applied to a coupled system that achieved simultaneous CaO/Ca(OH)2 THS and CO2 capture. The CO2 capture and THS performances of Ac‐CaO are always higher than those of calcined limestone owing to the preferable pore structure, whereas Ac‐CaO exhibits decreasing CO2 capture and THS performance resulting from sintering and the formation of CaCO3 from CaO or Ca(OH)2 with ambient CO2 during air cooling, respectively. In the coupled CaO/Ca(OH)2 THS and CO2 capture system, Ac‐CaO is subjected to 10 CO2 capture cycles, 30 THS cycles, 1 CO2 capture cycle, 10 THS cycles, 1 CO2 capture cycle, and 10 THS cycles sequentially. The hydration and dehydration conversions of Ac‐CaO in the 31st THS cycle reach 91.7 and 93.6%, respectively, which are 1.6 and 1.6 times higher than those recorded prior to the 11th CO2 capture cycle owing to the decomposition of CaCO3 during calcination. The carbonation conversion of Ac‐CaO achieves 89.9% in the 11th CO2 capture cycle, which is 22.3% higher than that recorded prior to the 10 THS cycles owing to reactivation from the hydration process during THS. The CO2 capture and CaO/Ca(OH)2 THS processes are enhanced in the coupled system using Ac‐CaO; therefore, the coupled system appears promising for CaO/Ca(OH)2 THS and CO2 capture. © 2020 Society of Chemical Industry and John Wiley & Sons, Ltd.